How Do Mergers Create Value? A Comparison of Taxes, Market Power, and Efficiency Improvements as Explanations for Synergies - Devos, Erik; Kadapakkam, Palani-Rajan; Krishnamurthy, Srinivasan (Review of Financial Studies, 2009)
There is little evidence in the literature on the relative importance of the underlying sources of merger gains. Prior literature suggests that synergies could arise due to taxes, market power, or efficiency improvements. Based on Value Line forecasts, we estimate the average synergy gains in a broad sample of 264 large mergers to be 10.03% of the combined equity value of the merging firms. The detailed data in Value Line projections allow for the decomposition of these gains into underlying operating and financial synergies. We estimate that tax savings contribute only 1.64% in additional value, while operating synergies account for the remaining 8.38%. Operating synergies are higher in focused mergers, while tax savings constitute a large fraction of the gains in diversifying mergers. The operating synergies are generated primarily by cutbacks in investment expenditures rather than by increased operating profits. Overall, the evidence suggests that mergers generate gains by improving resource allocation rather than by reducing tax payments or increasing the market power of the combined firm.